Dinâmica de nutrientes em florestas secundárias de terra firme na Amazônia Central - Oliveira, Fabiane Lima de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
Second growth, even when substantially different from the original forests in terms of floristics, plays important ecological functions, restoring some of the most important benefits to the system. This study aimed to determine the effects of differences in vegetation cover on the nutritional quality of litter and soil and recycling of nutrients. so samples were taken from soil, newly fallen litter and the litter-layer accumulated on the ground, in the PDBFF in BR 174, about 80 km north of Manaus. Three plots were sampled for each of the types of vegetation considered: ongoing pasture active, post-pasture second growth, post-harvest second growth, post-seringa second growth and primary forest. It was found that although the soil under pastures has higher concentrations of active organic matter and nutrients (K, Ca and Mg), the very low input of nutrients, especially nitrogen and basic cations provided by the litterfall into the system is leading it to the nutrient exhaustion in a short term period. In general and for the variable under study, the second growth vegetations in this study, all with more than 17 years of regeneration, are in such an advanced stage of secondary succession that masked any influences that either type of system or management might have had in the past. By the level of their recovery and function it was shown that those second growth surrounding the forest fragments are providing an important environmental service not only to recover biomass plant, restructuring the forest landscape and important ecological functions, but also in the recovery of the recycling of nutrients in soil including fixing carbon. 3
Keywords: Solos florestais; Nutrientes; Liteira